The seventh victim [large type] - Burton, Mary (Mary T.) (Center Point Large Print, 2013)
"Lara Church has only hazy memories of her long-ago attack. What she does have is a home in Austin, a job, and a chance at a normal life at last. Then Texas Ranger James Beck arrives on her doorstep with shattering news: The Strangler is back. And this time, he's in Austin"--Page 4 of cover.